GATA3 Expression in Common Gynecologic Carcinomas: A Potential Pitfall. (September 2019) - Terzic, Tatjana; Mills, Anne M.; Zadeh, Sarah; Atkins, Kristen A.; Hanley, Krisztina Z.
Abstract : GATA binding protein 3 (GATA3) immunohistochemistry is primarily used as a marker of breast and urothelial differentiation, particularly in metastatic settings. In the gynecologic tract it also serves a robust marker for mesonephric and trophoblastic tumors. However, expression has also been described in more common malignancies of gynecologic tract including ovarian, endometrial, and cervical carcinomas. Data on the distribution of GATA3 expression in gynecologic malignancies is somewhat limited, particularly across different histologic subtypes of ovarian, endometrial, and cervical carcinomas. To assess the rates of GATA3 expression among common gynecologic cancers of various histologic types, 100 ovarian carcinomas, 64 endometrial carcinomas/atypical hyperplasias, 16 cervical squamous cell carcinomas (SCCs), and 14 endocervical adenocarcinomas were evaluated by immunohistochemistry for GATA3 positivity. Eight percent of endometrial carcinomas expressed GATA3, including 2 serous carcinomas, 1 carcinosarcoma, and 1 case of atypical hyperplasia. Six percent of ovarian carcinomas were GATA3-positive including 2 clear cell carcinomas, 2 mucinous adenocarcinomas, and 2 high-grade serous carcinomas. Thirty-eight percent of cervical SCCs showed weak to moderate staining in up to 50% of tumor cells. All endocervical adenocarcinomas were entirely negative for GATA3. In summary, GATA3 shows focal weak to moderate expression in a subset of endometrial and ovarian carcinomas. In contrast, usual-type endocervical adenocarcinomas are typically negative for GATA3, which can be helpful in differentiating them from mesonephric proliferations or carcinomas. A larger proportion of cervical SCCs express GATA3, therefore caution should be exercised when using this stain in the setting of a lower genitourinary carcinomas.